Committing Millennials towards recycling and environmental preservation - Loureiro, S. M. C.; Kaufmann, H. R. (Journal of Promotion Management, 2016)
The purpose of this study is to analyze antecedents and consequences of affective commitment toward recycling and environmental preservation. The study hypothesizes that individuals whose recycling and environmental preservation has great meaning for their inner self and a positive influence on the way others see them will be more committed to recycling. A sample of 364 individuals was used to test the model. Findings reveal the importance of pleasant arousal in reinforcing self-expressive recycling in order to increase the affective commitment. Committed individuals seem to be more willing to sacrifice for the cause and spread the word in its favor